FAMILY MEDIATION: THE PERCEPTIONS AND EXPERIENCES OF UNMARRIED PARENTS AND MEDIATORS - Lagardien, Razia Nordien; Pretorius, Blanche; Terblanche, Susan (Social Work/Maatskaplike Werk, 2021)
While there have been significant developments regarding mediation, parental responsibilities and the rights of unmarried fathers, fathers remain challenged in acquiring their parental rights through mediation in terms of Section 21 of the Children’s Act 38 of 2005. The aim of this qualitative study was to understand the experiences of parents and mediators regarding mediation since the inception of the Children’s Act in 2007. Semi-structured interviews were conducted with unmarried fathers, unmarried mothers and mediators. Data were analysed using within-case analysis. The findings highlighted the positive experiences of mediation, challenges in mediation and strategies to enhance the quality of mediation.